Impact of plaques in the left coronary artery on wall shear stress and pressure gradient in coronary side branches - Chaichana, Thanapong; Sun, Zhonghua; Jewkes, James (Taylor & Francis, 2014)
In this study, we investigate plaques located at the left coronary bifurcation. We focus on the effect that the resulting changes in wall shear stress (WSS) and wall pressure stress gradient (WPSG) have on atherosclerotic progress in coronary artery disease. Coronary plaques were simulated and placed at the left main stem and the left anterior descending to produce >50% narrowing of the coronary lumen. Computational fluid dynamics analysis was carried out, simulating realistic physiological conditions that show the in vivo cardiac haemodynamic. WSS and WPSG in the left coronary artery were calculated and compared in the left coronary models, with and without the presence of plaques during cardiac cycles. Our results showed that WSS decreased while WPSG was increased in coronary side branches due to the presence of plaques. There is a direct correlation between coronary plaques and subsequent WSS and WPSG variations based on the bifurcation plaques simulated in the realistic coronary models.